MARC 21 : - Aswal, Rajendra Singh (Ess Ess Publications, 2004)
Contents of material: 1/ What is MARC and why is it necessary? 2/ Types of MARC format and their disignation. 3/ MARC 21 formats: For the 21st century. 4/ Sample format of MARC 21 with example . 5/ UNIMARC to MARC 21 conversion specifications. 6/ MARC 21 format for authority data. 7/ MARC 21 format for bibliographic record. 8/ MARC 21 format for holding data.